2017
DOI: 10.1097/md.0000000000009300
|View full text |Cite
|
Sign up to set email alerts
|

A possible synergistic effect of MTHFR C677T polymorphism on homocysteine level variations increased risk for ischemic stroke

Abstract: Background:Homocysteine (Hcy) plays an important role in vascular function and Hcy level contributes to pathogenesis of ischemic stroke (IS). MTHFR gene polymorphism may have effects on IS risks by influencing the Hcy metabolic pathway. In the present study, a case–control study was designed to evaluate the relationship among MTHFR C677Tpolymorphism, plasma Hcy level, and susceptibility of IS in Chinese population.Methods:A total of 300 patients with IS and 261 matched control subjects were recruited. Plasma H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
(18 reference statements)
2
18
0
2
Order By: Relevance
“…Firstly, no obvious heterogeneities were detected in overall analyses for two investigated polymorphisms, which indicated that eligible studies could be considered as homogeneous, and thus synthesize the results of these studies is statistically feasible. Secondly, previous experimental studies have shown that the C to T substitution of rs1801133 (substitution of valine for alanine) and A to C substitution of rs1801131 (substitution of glutamate for alanine) could lead to reduced enzymatic activity and result in hyperhomocysteinemia, which may partially explain our positive findings (Li et al, ; Li, Dai, Zheng, Liu, & Huang, ). Thirdly, the pathogenic mechanism of glaucoma is quite complex, and hence it is unlikely that a single gene polymorphism can significantly contribute to its development.…”
Section: Discussionmentioning
confidence: 68%
“…Firstly, no obvious heterogeneities were detected in overall analyses for two investigated polymorphisms, which indicated that eligible studies could be considered as homogeneous, and thus synthesize the results of these studies is statistically feasible. Secondly, previous experimental studies have shown that the C to T substitution of rs1801133 (substitution of valine for alanine) and A to C substitution of rs1801131 (substitution of glutamate for alanine) could lead to reduced enzymatic activity and result in hyperhomocysteinemia, which may partially explain our positive findings (Li et al, ; Li, Dai, Zheng, Liu, & Huang, ). Thirdly, the pathogenic mechanism of glaucoma is quite complex, and hence it is unlikely that a single gene polymorphism can significantly contribute to its development.…”
Section: Discussionmentioning
confidence: 68%
“…Wang et al (2018) found that the SNP of the MTHFR rs1801133 and NAFLD had a potential synergistic effect on elevated Hcy levels. Li et al (2017) found that the plasma Hcy levels of different genotypes of the MTHFR rs1801133 showed the tendency of the TT genotype >CT genotype >CC genotype. They concluded that a possible synergistic effect of the MTHFR rs1801133 SNP on plasma Hcy levels increased the risk of IS.…”
Section: Discussionmentioning
confidence: 94%
“…As a sulfur-containing amino acid, Hcy is an important intermediate product for the metabolism of methionine. Hcy has an important role in vascular function (Li et al, 2017). Elevated Hcy levels can predispose vascular smooth muscle cells and endothelial cells to injury, which leads to activation of coagulation factors, expression of plasminogen activator inhibitor, endothelial proliferation and so on (Hainsworth et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth to underline that probable role of MTHFR gene www. journals.viamedica.pl/ginekologia_polska polymorphisms in the etiology of intrauterine fetal death may be a result of hyperhomocysteinemia caused by these genetic variants [24][25][26].…”
Section: Discussionmentioning
confidence: 99%